The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/intqhc/mzt087
|View full text |Cite
|
Sign up to set email alerts
|

Is culture associated with patient safety in the emergency department? A study of staff perspectives

Abstract: Staff identified several dimensions of safety culture that are associated with staff-reported safety in the ED. Physicians and nurses identified distinct dimensions of safety culture as associated with reported level of patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 33 publications
10
45
0
3
Order By: Relevance
“…[28] The authors argued that an incident reporting system not only leads to changes in care processes, but also leads to modifying staff attitudes and knowledge, while having an overall positive effect on safety practice. [28] This finding is also consistent with a crosssectional survey [34] that found associations, such as "teamwork across units", "frequency of event reporting", "communication openness", "feedback about and learning from errors", "hospital management support for patient safety", were statistically significant, and concluded that these factors are important predictors of staff-reported safety in the Emergency Department (ED). This is also supported by Clarke, [27] who concluded that the reporting of near-miss and unsafe conditions was considered an important component of hospitalbased safety initiatives.…”
Section: Reportingsupporting
confidence: 82%
“…[28] The authors argued that an incident reporting system not only leads to changes in care processes, but also leads to modifying staff attitudes and knowledge, while having an overall positive effect on safety practice. [28] This finding is also consistent with a crosssectional survey [34] that found associations, such as "teamwork across units", "frequency of event reporting", "communication openness", "feedback about and learning from errors", "hospital management support for patient safety", were statistically significant, and concluded that these factors are important predictors of staff-reported safety in the Emergency Department (ED). This is also supported by Clarke, [27] who concluded that the reporting of near-miss and unsafe conditions was considered an important component of hospitalbased safety initiatives.…”
Section: Reportingsupporting
confidence: 82%
“…Different perceptions of safety culture exist among health care professionals at different levels. One example of this is that nurses are more likely than doctors or managers to report barriers to patient safety (Braithwaite et al, ; Buerhaus et al, ; Makary et al, ; Singer, Gaba, et al, ; Singer, Lin, Falwell, Gaba, & Baker, ; Verbakel et al, ; Verbeek‐Van Noord, Wagner, Van Dyck, Twisk, & De Bruijne, ). These differences indicate that those at higher levels of the system may be unaware of the factors impacting patient safety, as a result, they are less likely to allocate resources to improve them (Buerhaus et al, ; Singer, Falwell, Gaba, & Baker, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have called for clarification of the relationship between safety culture and patient safety outcomes (Clarke, ; Sorra & Dyer, ). In this review, studies found that safety culture improved safety outcomes including accident prevention and safety compliance as well as less adverse events (Clarke, ; Halligan & Zecevic, ; Jackson, Sarac, & Flin, ; Neal & Griffin, ; Singer, Gaba, et al, ; Verbeek‐Van Noord et al, ; Wang et al, ) . However, other studies did not support this relationship (Ausserhofer et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Estudo realizado em unidades de urgência e emergência da Holanda identificou dimensões positivas da cultura associadas com a segurança do paciente (21) . Outro, realizado em 68 hospitais libaneses, com 6.807 profissionais de saúde, encontrou indícios significativos da relação da cultura positiva com a segurança do paciente (22) .…”
Section: Discussionunclassified